Gangguan depresi berhubungan dengan status gizi pasien psikogeriatri di RSJ DR. Radjiman Wediodiningrat, Malang - Wawan Agung Prasetyo; Probosuseno Probosuseno; Sumarni Sumarni (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2015)
ABSTRACTBackground: Nutritional problem in psychogeriatric patients has not got much attention in geriatric psychiatry. However, malnutrition is likely to have a major impact on mental and physical condition of the elderly. In patients with depression, nutritional problems have a major contribution in determining food intake and nutrient of elderly, because depression can cause loss of appetite which impact on the nutritional status of elderly.Objectives: To determine the association between depression with nutritional status of geriatric psychiatry patients at DR. Radjiman Wedioningrat Mental Hospital, Lawang District of Malang.Methods: This was an observational study with cross sectional design. Subjects were geriatric psychiatry inpatients at Radjiman Wediodiningrat Mental Hospital Lawang Distric of Malang. Depression status was assessed using the short form of the geriatric depression scale (GDS-15). Food intake were collected using plate waste (visual comstock methods) and 24 hours food recall methods. Nutritional status was assessed using the mini nutritional assessment-Taiwan version-1 (MNA-T1). The data was analysed by univariat, bivariat, and multivariat.Results: Out of total subject of the study (52 people), 53.9% were depressed and 50% were malnourished. Dominant factor that affect nutritional status was moderate depression (OR=11.14). Bivariat analysis showed that there was a significant association between functional status, energy intake, and protein intake with nutritional status. There was not significantly association between energy intake and protein intake with depression status. There was a significant association between depression status and nutritional status of geriatric psychiatry patients (OR=11.14, 95% CI:1.7-73.14).Conclusions: There was a significant association between depression status and nutritional status.KEYWORDS: depression status, geriatric psychiatric, nutritional statusABSTRAKLatar belakang: Masalah gizi pada pasien psikogeriatri kurang mendapat perhatian dalam penelitian psikiatri geriatri, padahal malnutrisi cenderung memiliki dampak yang besar terhadap kondisi mental dan fisik pada lansia. Pada pasien depresi, masalah gizi mempunyai kontribusi yang besar dalam menentukan asupan makanan dan zat gizi lansia karena depresi dapat menyebabkan kehilangan nafsu makan yang berdampak pada penurunan status gizi lansia.Tujuan: Mengetahui hubungan antara gangguan depresi dengan status gizi pasien psikogeriatri di RSJ Dr. Radjiman Wediodiningrat, Lawang, Malang.Metode: Penelitian ini bersifat observasional dengan rancangan cross sectional. Subjek penelitian ini adalah pasien psikogeriatri di ruang rawat inap psikogeriatri RSJ Dr. Radjiman Wediodiningrat Lawang. Data status depresi diukur dengan geriatric depression scale-15 (GDS-15). Data asupan zat gizi menggunakan metode visual Comstock dan recall 24 jam. Data status gizi ditentukan berdasarkan (MNA-T1). Data dianalisis secara univariat, bivariat, dan multivariat.Hasil: Dari total subjek penelitian (52 orang), sebesar 53,9% mengalami depresi dan sebesar 50% mengalami malnutrisi. Faktor yang paling dominan mempengaruhi status gizi adalah status depresi sedang (OR=11,14). Hasil uji bivariat menunjukkan ada hubungan yang bermakna antara status fungsional,asupan energi, asupan protein, dan status depresi dengan status gizi. Hasil uji multivariat menunjukkan ada hubungan yang signifikan antara status depresi dengan status gizi (OR=11,14, 95% CI:1,7-73,14).Kesimpulan: Ada hubungan signifikan antara status depresi dengan status gizi pada pasien psikogeriatri.KATA KUNCI: status depresi, pasien psikogeriatri, status gizi